Оцінка чутливості Daphnia magna до дії наноаквацитратів цинку in vivo - Кравченко, Ольга; Максін, Віктор; Kravchenko, Olga; Maksin, Viktor (Східноєвропейський Національний університет імені Лесі Українки, 2015)
Досліджено токсичність цитратованих наночасток цинку, отриманих ерозійно-вибуховою нанотехно- логією, для D. magna методами біотестування. Визначено токсикометричні показники за допомогою пробіт- аналізу. Оцінено можливість використання різних концентрацій препарату на практиці. The research of the toxicity of zinc naтoaquacitrates in various concentrations for modeling test-object of aqua toxicology (Daphnia magna) by bioassay method was conducted. It was identified the toxic metric parameters using probit-analysis According to the results of 96-hour experiments, the median concentration zinc nanoaquacitrates was 0,067 ± 0,008 mg /l. It was experimentally proved that the range of 0,1–1 mg / dm3 of zinc nanoparticle was acutely toxic to Daphnia and completely inhibited all essential functions in the body of the test object. Concentration in the range of 0,05 mg/dm3 was potentially dangerous for daphnia because impact on reproductive function due to loss of eggs and embryos in the brood pouch. These violations invariably led to changes of the age and spatial structure of populations in natural ecosystems. The concentrations of 0,01 mg / dm3 were safe to plankton test-objects that’s why can be used for practical purposes.
Sensitivity Daphnia Magna to Action of zinc Nanoaquacitrates in Vivo.
Keywords: токсичність; наноаквацитрати; Daphnia magna; біотестування; пробіт-аналіз; toxicity; nanoaquacirtate; Daphnia magna; boiassay; probit-analysis